Development of Novel C–H Bond Transformations and Their Application to the Synthesis of Organic Functional Molecules - Kuninobu, Yoichiro (Synlett, 2018)
This personal account summarizes our recent progress in the development of C–H transformations. We achieved ortho-selective C–H borylations and silylations by using Lewis acid–base interaction between two substrates and we achieved meta- and ortho-selective C–H borylations by using hydrogen bonding or Lewis acid–base interaction between a hydrogen donor or Lewis acid unit of a ligand and a functional group of a substrate. Regioselective C–H trifluoromethylations and related reactions of six-membered heteroaromatic compounds were realized at their 2- and 4-positions and at their benzylic positions. In addition, we developed C–H transformations directed towards the synthesis of organic functional materials, such as highly soluble polyimides or π-conjugated molecules containing either heteroatom(s) or a Lewis acid–base interaction.1 Introduction2 Regioselective C–H Transformations Controlled by Noncovalent Bond Interactions2.1 Regioselective C–H Transformations Controlled by Lewis Acid–Base Interaction between Two Substrates2.2 Regioselective C–H Transformation Controlled by Hydrogen Bonding between Ligand and Substrate2.3 Regioselective C–H Transformations Controlled by Lewis Acid–Base Interactions between Ligands and Substrates3 Trifluoromethylation and Related Transformations of Six-Membered Heteroaromatic Compounds3.1 2-Position-Selective C–H Trifluoromethylation of Six-Membered Heteroaromatic Compounds3.2 4-Position-Selective C–H Trifluoromethylation of Six-Membered Heteroaromatic Compounds3.3 Benzyl Position-Selective C–H Trifluoromethylation of Six-Membered Heteroaromatic Compounds4 C–H Transformations Leading to the Synthesis of Organic Functional Materials4.1 Heteroatom-Containing π-Conjugated Molecules4.2 π-Conjugated Molecules Containing a Lewis Acid–Base Interaction4.3 Soluble Polyimide Derivatives5 Conclusions
Keywords: C–H transformations; regioselectivity; noncovalent interactions; hydrogen bonding; borylation; silylation